Application Of The Problem Solving Learning Model In Improving Numeracy Skills In Class IV Students Of SDN - Asmah, St; Hastati, Sri; Nurdiansyah, Erwin (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This research aims to improve the numeracy skills of mathematics problem-solving of grade IV students of SDN Tanetea by using problem-solving learning model on square, rectangular and triangular flat building materials. The subjects of this study are grade IV students of SD N Tanetea, Gowa Regency for the 2023/2024 school year, totaling 23 students. This type of research is Classroom Action Research that is carried out in 2 cycles, each cycle is carried out 2 times. The data collection was carried out by tests, observation sheets of teachers and students as the level of implementation and achievement in using the problem-solving learning model. The results of problem-solving skills can be seen from the results of the pre-test, cycle I and cycle II. In the pre-test, the average score of the success indicator was 42.86 with the percentage of learning completeness with total score 4%, it was lack. In the first cycle, there was an increase with an average score of 71.15 with a percentage of learning completion with total score 65% and in the second cycle there was an increase with an average score 79.57 with a percentage of learning completion with a total success score of 87%. Based on the results of the study, it can be concluded that the problem-solving learning model can improve problem-solving numeracy skills in grade IV students of SD Negeri Tanetea, Gowa Regency.